On the Recovery of Galaxy Properties from SED Fitting Solutions. (4th January 2016) - Magris C., Gladis; Mateu P., Juan; Mateu, Cecilia; Bruzual A., Gustavo; Cabrera-Ziri, Ivan; Mejía-Narváez, Alfredo
Abstract: We explore the ability of four different inverse population synthesis codes to recover the physical properties of galaxies from their spectra by SED fitting. Three codes, DynBaS, TGASPEX, and GASPEX, have been implemented by the authors and are described in detail in the paper.STARLIGHT, the fourth code, is publicly available. DynBaS selects dynamically a different spectral basis to expand the spectrum of each target galaxy, and TGASPEX uses an unconstrained age basis, whereas GASPEX andSTARLIGHT use for all fits a fixed spectral basis selected a priori by the code developers. Variable and unconstrained basis reflect the peculiarities of the fitted spectrum and allow for simple and robust solutions to the problem of extracting galaxy parameters from spectral fits. We assemble a Synthetic Spectral Atlas of Galaxies (SSAG), 3 comprising 100, 000 galaxy spectra corresponding to an equal number of star formation histories based on the recipe of Chen et al. We select a subset of 120 galaxies from SSAG with a color distribution similar to that of local galaxies in the seventh data release (DR7) of the Sloan Digital Sky Survey (SDSS), and produce 30 random noise realizations for each of these spectra. For each spectrum, we recover the mass, mean age, metallicity, internal dust extinction, and velocity dispersion characterizing the dominant stellar population in the problem galaxy. All methods produce almost-perfect fits to the target spectrum, but the recovered physical parameters can differ significantly. Our tests provide a quantitative measure of the accuracy and precision with which these parameters are recovered by each method. From a statistical point of view, all methods yield similar precisions, whereas DynBaS produces solutions with minimal systematic biases in the distributions of residuals for all of these parameters. We caution the reader that the results obtained in our consistency tests represent lower limits to the uncertainties in parameter determination. Our tests compare theoretical galaxy spectra built from the same synthesis models used in the fits. Using different synthesis models and the lack of particular stellar types in the synthesis models but present in real galaxies will increase these errors considerably. Additional sources of error expected to be present in real galaxy spectra are not easy to emulate, and again will result in larger errors.